Aberrant Pancreatic Tissue in a Mediastinal Enteric Duplication Cyst: A Rarity with Review of Literature - Meha Mansi; Nidhi Mahajan; Sonam Mahana; C. R. Gupta; Anup Mohta (Case Reports in Gastrointestinal Medicine)
Mediastinal enteric duplication cysts are a rare congenital malformation encountered mainly in neonates and infants. It is a distinct entity within the family of foregut duplication cysts. It can present with respiratory distress due to mass effect and hence surgical excision is the preferred treatment. Histologically, it is characterised by a double layered smooth muscle wall with intestinal lining epithelium. We report a case of mediastinal enteric duplication cyst with aberrant pancreatic tissue in a neonate due to its rarity and early presentation. A neonate presented with respiratory distress and a cystic mass in the right posterior mediastinum. The lesion was excised and on histopathological analysis the diagnosis of mediastinal enteric duplication cyst was made. Also, aberrant pancreatic tissue which has been reported rarely was noted in this case. We discuss this case and review similar cases reported in literature.